Solución para el aprendizaje, implementación y seguimiento de cultivos urbanos medicinales (2021)
The pandemic generated by COVID-19 has demonstrated worldwide, and even more so in Colombia, the lack of care capacity of the health system. To optimize this capacity, it is possible to make use of traditional and complementary medicine by users, which was recognized by the WHO at the Congress on Traditional Medicine held in Beijing in 2008 and by the Ministry of Health through the document “ Technical guidelines for the articulation of medicines and alternative and complementary therapies, within the framework of the general system of social security in health ”. However, it is clear that in the urban sector there is an agricultural culture that facilitates the cultivation of medicinal plants